Chestnut Red Stain: Identification of the fungi associated with the costly discolouration of Castanea sativa. Issue 4 (24th February 2017) - Yurkewich, J. I.; Castaño, C.; Colinas, C.
Summary: In Europe, fungal pathogens have reduced the overall productivity of sweet chestnut ( Castanea sativa) stands and continue to threaten the economic viability of forestry operations. Chestnut Red Stain (CRS) in north‐eastern Spain, locally referred to as Roig, is capable of decreasing the market value of chestnut timber to the point of rendering chestnut coppices uneconomical. Despite its economic importance, the specific cause of this red discolouration is unknown. With the objective of verifying the presence of fungi within the symptomatic wood, and identifying the fungus or suite of fungi associated with the red stain, wood samples were collected and cultured from 37 stumps found in eight recently harvested stands in the Montseny and Montnegre‐Corredor Natural Parks. To separate the fungi associated with CRS from other species inhabiting the chestnut wood, the origin of each fungal culture was mapped in every stump. The fungi were isolated from cultures and identified by sequencing the ITS region. The results provide insight into the fungal community inhabiting chestnut wood and the potential cause of CRS; nine species were identified including two species known to cause decay in chestnut. One of them, Fistulina hepatica, appears to be a likely candidate for the causal agent of CRS. This is the first study reporting the fungi associated with CRS and opens the door to new epidemiological studies focused on F. hepatica .